A metal compound with adjustable valence and its preparation and application
By introducing CNT into lithium-sulfur batteries to regulate the valence of cobalt in CoSe2, forming CNT-CoSe2, the problems of easy soluble polysulfides and slow oxidation reaction kinetics in lithium-sulfur batteries are solved, and catalytic activity and electrochemical performance are improved.
Patent Information
- Application Number
- CN202310104038.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-02-13
AI Technical Summary
The intermediate product of lithium sulfur batteries is easily soluble in the electrolyte, resulting in slow shuttle effect and oxidation reaction kinetics, resulting in low utilization rate of active substances, poor cycle stability and low rate performance, limiting the development and application of lithium sulfur batteries.
By introducing carbon nanotubes (CNTs) to regulate the valence of cobalt in CoSe2, CNT-CoSe2 is formed, and its catalytic activity is improved. The method includes in-situ recombination of CNT and Co-MOF and reacting with selenium powder at a high temperature of 400 to 600°C, controlling the type, dosage and reaction temperature of CNT to regulate the valence state of Co.
By regulating the valence of Co in CoSe2, catalytic activity is improved and the electrochemical performance of lithium-sulfur batteries is enhanced, including improving cycle stability and rate performance.
Smart Images

Figure CN115986123B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a metal compound with adjustable valence and a preparation method thereof. Background Art
[0002] Polysulfides, the intermediate products of lithium-sulfur battery charging and discharging, are easily soluble in the electrolyte to form a shuttle effect, and their oxidation reaction kinetics are slow, resulting in low utilization of active substances, poor cycle stability and low rate performance of lithium-sulfur batteries, which restricts their development and application. Summary of the invention
[0003] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a metal compound with adjustable valence and a preparation method thereof, and with respect to CoSe2 as a positive electrode sulfur catalyst for lithium-sulfur batteries, CNTs are introduced to regulate the valence of cobalt in CoSe2 and improve its catalytic activity.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A metal compound with adjustable valence, expressed as: CNT-CoSe2; wherein CNT represents carbon nanotube, the introduction of CNT makes Co in CoSe2 2+ The content of Co increases 3+ The content of is reduced, thereby regulating the valence state of Co in CoSe2.
[0006] In an embodiment of the present invention, the CNT is in situ composited with Co-MOF and reacts with selenium powder at a high temperature of 400 to 600° C. to form CNT-CoSe2. The valence state of Co in CoSe2 is regulated by controlling the type and amount of CNT and the temperature of the reaction with selenium powder.
[0007] In the embodiment of the present invention, in the CoSe2, Co 2+ / Co 3+ The adjustable ratio range is 0.86:1 to 0.56:0.
[0008] In the embodiment of the present invention, the carbon nanotubes are one or more of hydroxylated carbon nanotubes, carboxylated carbon nanotubes or other functionalized nanotubes containing functional groups.
[0009] The present invention also provides a method for preparing the metal compound with adjustable valence, comprising the following steps:
[0010] Step (1), ultrasonically dispersing carbon nanotubes in anhydrous methanol, adding hexadecyltrimethylammonium bromide and stirring to dissolve, and then adding cobalt nitrate hexahydrate to dissolve to obtain a mixed solution;
[0011] Step (2), pouring methanol containing dimethylimidazole into the mixed solution and stirring, then standing and aging at room temperature, and washing by centrifugation with ethanol to obtain CNT-Co-MOF;
[0012] Step (3), after mixing the CNT-Co-MOF with selenium powder, heat-treating the mixture in an inert atmosphere to obtain CNT-CoSe2.
[0013] In the embodiment of the present invention, the mass ratio of hexadecyltrimethylammonium bromide to carbon nanotubes is 1:5-1:10, the mass ratio of carbon nanotubes to cobalt nitrate hexahydrate is 1:8-1:10, and the mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 1:1-1.5:1.
[0014] In the embodiment of the present invention, the mass ratio of the CNT-Co-MOF to the selenium powder is 1:1.8 to 1:2.
[0015] In the embodiment of the present invention, in the step (3), the heat treatment parameters are 400-600° C. in an inert atmosphere for 2-3 hours.
[0016] The metal compound with adjustable valence described in the present invention can be used as a sulfur catalyst for lithium-sulfur batteries.
[0017] In an embodiment of the present invention, CNT-CoSe2 is mixed with sulfur and used as a positive electrode material for a lithium-sulfur battery; alternatively, a sulfur-carbon composite material is used as the positive electrode, CNT-CoSe2 is mixed with PVDF, an NMP slurry is added, and the mixture is coated on a PP diaphragm to obtain a CNT-CoSe2-modified diaphragm, and a lithium sheet is used as the negative electrode to assemble a button battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) In the present invention, compared with CoSe2 obtained without adding CNT, the valence of cobalt is regulated after the introduction of CNT (specifically, Co 2+ / Co 3+ The proportion of carbon materials increased to varying degrees), which improved their catalytic activity and provided a new idea for the composite modification of carbon materials and metal compounds.
[0020] (2) CNT has a large specific surface area and excellent conductivity, which can improve the specific surface area and conductivity of the composite material and help the composite material catalyze the conversion of lithium polysulfide.
[0021] (3) The preparation method for regulating the valence of metal compounds of the present invention has simple steps, simple reaction equipment, and the quality of the obtained product is uniform and stable. It is a material and preparation method that can be prepared on a large scale and efficiently, and can be promoted and applied to other fields such as catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the X-ray diffraction (XRD) pattern of CoSe2 and CNT-CoSe2 prepared in Example 1.
[0023] Figure 2 This is the X-ray photoelectron spectroscopy (XPS) graph of CoSe2 and CNT-CoSe2 prepared in Example 1.
[0024] Figure 3 Cyclic voltammetry (CV) diagram of Li2S6 symmetric cell in which CoSe2 and CNT-CoSe2 prepared in Example 1 are used as sulfur catalysts.
[0025] Figure 4 The rate performance of lithium-sulfur batteries assembled with commercial PP separators modified with CoSe2 and CNT-CoSe2 prepared in Example 1.
[0026] Figure 5 This is the XPS graph of CNT-CoSe2 prepared in Example 2. DETAILED DESCRIPTION
[0027] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.
[0028] Metal selenides have high conductivity and high catalytic activity, which can promote the conversion of lithium polysulfide and improve its redox kinetics, thereby alleviating the shuttle effect of lithium polysulfide and improving the electrochemical performance of lithium-sulfur batteries. However, the valence of the metal elements in cobalt selenide will affect the catalytic activity of cobalt selenide in the reaction process of lithium-sulfur batteries. Therefore, regulating the valence of cobalt selenide is of great significance for catalyzing the conversion of lithium polysulfide.
[0029] The present invention aims to provide a metal compound cobalt selenide with adjustable valence, which is in situ composited with carbon nanotubes (CNT) and Co-MOF and reacted with selenium powder at a high temperature of 400-600°C, and its expression is CNT-CoSe2. The introduction of CNT in the present invention can make Co in CoSe2 2+ The content of Co increases 3+ The content of CNT is reduced, thereby regulating the valence state of Co in CoSe2. The principle is that the surface functional groups of CNTs adsorb cobalt ions through electrostatic interactions and serve as nucleation sites for Co-MOF, interacting electronically with cobalt during the in-situ composite process of Co-MOF.
[0030] Specifically, the valence of Co in CoSe2 can be regulated by controlling one or a combination of factors such as the type and amount of CNT and the temperature of the reaction with selenium powder. 2+、Co 3+ The characteristic peak shifts toward the low binding energy direction, and Co 2+ and Co 3+ The ratio of Co to CNT changes, thereby regulating the valence of Co. 2+ The content of Co 2+ The content.
[0031] In the embodiment of the present invention, the carbon nanotubes may be one or more of hydroxylated carbon nanotubes, carboxylated carbon nanotubes or other functionalized nanotubes containing functional groups.
[0032] The present invention also provides a method for preparing the metal compound with adjustable valence, comprising the following steps:
[0033] Step (1), ultrasonically dispersing carbon nanotubes in anhydrous methanol, adding hexadecyltrimethylammonium bromide and stirring to dissolve, and then adding cobalt nitrate hexahydrate to dissolve to obtain a mixed solution.
[0034] In this step, the mass ratio of hexadecyltrimethylammonium bromide to carbon nanotubes can be 1:5-1:10, and the mass ratio of carbon nanotubes to cobalt nitrate hexahydrate can be 1:8-1:10. Among them, the main function of hexadecyltrimethylammonium bromide is to promote the in-situ composite of CNT and Co-MOF, the main function of cobalt nitrate hexahydrate is to be the cobalt source of Co-MOF, providing cobalt ions as nodes of Co-MOF, and the main function of anhydrous methanol is to be used as a solvent to dissolve cobalt nitrate hexahydrate and dimethylimidazole.
[0035] Step (2), pouring methanol containing dimethylimidazole into the mixed solution and stirring, then standing and aging at room temperature, and washing by centrifugation with ethanol to obtain CNT-Co-MOF.
[0036] In this step, the amount of dimethylimidazole used is 1:1 to 1.5:1 in mass ratio with cobalt nitrate hexahydrate, and its role is to coordinate with cobalt ions as an organic ligand to form Co-MOF. In this step, the aging time at room temperature is generally 12 to 24 hours.
[0037] Taking carboxylated carbon nanotubes as an example, the carboxyl functional groups on the surface of the nanotubes will adsorb cobalt ions through electrostatic interactions and serve as nucleation sites for the metal organic framework Co-MOF, which is conducive to the assembly of cobalt ions and 2-methylimidazole to form CNT-Co-MOF in-situ composite materials. Different types of CNTs will produce different composite materials due to differences in functional groups.
[0038] Step (3), after mixing the CNT-Co-MOF with selenium powder, heat-treating the mixture in an inert atmosphere to obtain CNT-CoSe2.
[0039] In this step, the mass ratio of CNT-Co-MOF to selenium powder is 1:1.8 to 1:2. The role of selenium powder is to form selenium vapor at high temperature and react with Co-MOF to obtain CoSe2.
[0040] In this step, the heat treatment parameters are 400-600° C. in an inert atmosphere for 2-3 hours.
[0041] The mechanism of obtaining CNT-CoSe2 by heat treatment is that selenium powder forms selenium vapor during the heat treatment process and enters the Co-MOF that undergoes pyrolysis due to the high temperature. At this time, due to the breaking of the valence bond, the selenium atom reacts with the cobalt ion to generate CoSe2, and the dimethylimidazole in the Co-MOF is carbonized to form a carbon layer surrounding the CoSe2 nanoparticles, while the close connection between CNT and CoSe2 is still maintained after selenization.
[0042] The following are several specific embodiments of the present invention.
[0043] Example 1
[0044] (1) 50 mg of hydroxy carbon nanotubes (CNT) were ultrasonically dispersed in 50 mL of anhydrous methanol, 10 mg of hexadecyltrimethylammonium bromide was added, and the mixture was stirred for 1 h. Subsequently, 498 mg of cobalt nitrate hexahydrate was dissolved in the above mixed solution.
[0045] (2) Pour 50 mL of methanol containing 656 mg of dimethylimidazole into the mixed solution of step (1), stir for 10 min, let stand at room temperature for 24 h, wash with ethanol by centrifugation 5 times, and dry in vacuum at 60 ° C for 12 h to obtain CNT-Co-MOF.
[0046] (3) CNT-Co-MOF and selenium powder were mixed in a mass ratio of 1:2 and heated in Ar gas at a rate of 2 °C min -1 The temperature was raised to 450°C for 2 h to obtain CNT-CoSe2. The obtained sample was subjected to X-ray diffraction (XRD) analysis. Figure 1 As shown in the figure, CoSe2 can be obtained without adding CNT, and its diffraction peaks all belong to PDF#88-1712. The 25° diffraction peak of the sample obtained after adding CNT comes from CNT, and the other diffraction peaks are consistent with CoSe2. The obtained samples were analyzed by X-ray photoelectron spectroscopy (XPS), as shown in the figure. Figure 2 As shown in Figure 2, compared with the Co 2p XPS of CoSe2, the Co 2+ 、Co 3+ The characteristic peak shifts toward the low binding energy direction, and Co 2+ / Co 3+ The ratio of CNTs increased from 1.79 to 3.78, which indicates that the introduction of CNTs increases the 2+The content of Co 3+ The content of Co regulates the valence state of Co.
[0047] (4) S and Li2S were added to a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) at a molar ratio of 5:1 and stirred at 60 °C for 24 h to prepare 0.2 mol L -1 Li2S6 solution, in which the volume ratio of DOL and DME is 1:1. CNT-CoSe2 and polyvinylidene fluoride (PVDF) are mixed at a mass ratio of 9:1 and ground for 30 minutes, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added and stirred for 8 hours. After coating and drying, the electrode is made and the Li2S6 symmetric battery is assembled. The cyclic voltammetry curves of CoSe2 and CNT-CoSe2 symmetric batteries are tested between -1 and 1V. Figure 3 As shown, compared with CoSe2, CNT-CoSe2 has a larger peak response current and smaller polarization for Li2S6, indicating that the CNT-CoSe2 composite material has a better catalytic effect on the conversion of lithium polysulfide, that is, the introduction of CNT to regulate the valence state of Co in CoSe2 improves its catalytic activity.
[0048] (5) Using sulfur-carbon composite materials as the positive electrode, CoSe2 and CNT-CoSe2 were mixed with AB carbon and PVDF in a mass ratio of 4:5:1, and an appropriate amount of NMP was added to the mixed slurry, and then coated on a commercial PP diaphragm to obtain CoSe2 and CNT-CoSe2 modified diaphragms. Using lithium sheets as negative electrodes, a DOL / DME (v:v=1:1) mixed solution containing 1M lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 1wt.% LiNO3 was used as the electrolyte. A 2032 button cell was assembled in an argon-filled glove box, and its rate performance was tested. Figure 4 As shown in the figure, compared with CoSe2, the rate performance of CNT-CoSe2 is significantly improved, especially at 2C rate, the specific capacity is increased from 546.86 mAh g -1 Increased to 735.49 mAh g -1 , showing that the introduction of CNTs to regulate the valence of CoSe2 has a significant improvement effect on the electrochemical performance of lithium-sulfur batteries.
[0049] Example 2
[0050] (1) 50 mg of carboxyl carbon nanotubes (CNT) were ultrasonically dispersed in 50 mL of anhydrous methanol, and 10 mg of hexadecyltrimethylammonium bromide was added and stirred for 1 h. Subsequently, 498 mg of cobalt nitrate hexahydrate was dissolved in the above mixed solution;
[0051] (2) Pour 50 mL of methanol containing 656 mg of dimethylimidazole into the mixed solution of step (1) and stir for 10 min. After standing at room temperature for 24 h, wash the mixture with ethanol by centrifugation several times and dry it at 60 °C for 12 h to obtain CNT-Co-MOF.
[0052] (3) CNT-Co-MOF and selenium powder were mixed in a mass ratio of 1:2 and annealed in an inert atmosphere to obtain CNT-CoSe2. The XPS spectrum of the obtained sample is shown in Figure 5 As shown, Figure 2 Compared with the Co 2p XPS of CoSe2 in CNT-CoSe2, the Co 2+ The characteristic peak of Co shifts toward the low binding energy direction, and 3+ The characteristic peak also disappears, which means that the introduction of carboxyl CNTs also changes the valence state of Co.
[0053] Example 3
[0054] (1) 50 mg of hydroxy carbon nanotubes (CNT) were ultrasonically dispersed in 50 mL of anhydrous methanol; 10 mg of hexadecyltrimethylammonium bromide was added and stirred for 1 h. Subsequently, 498 mg of cobalt nitrate hexahydrate was dissolved in the above mixed solution;
[0055] (2) Pour 50 mL of methanol containing 656 mg of dimethylimidazole into the mixed solution of step (1) and stir for 10 min. After standing at room temperature for 24 h, wash the mixture with ethanol by centrifugation several times and dry it in vacuum at 60 °C for 12 h to obtain CNT-Co-MOF.
[0056] (3) CNT-Co-MOF and selenium powder were mixed in a mass ratio of 1:2 and kept at 450°C for 2 h in a nitrogen atmosphere to obtain CNT-CoSe2.
[0057] Example 4
[0058] (1) 100 mg of functionalized carbon nanotubes (CNT) were ultrasonically dispersed in 80 mL of anhydrous methanol; 10 mg of hexadecyltrimethylammonium bromide was added and stirred for 1 h. Subsequently, 800 mg of cobalt nitrate hexahydrate was dissolved in the above mixed solution;
[0059] (2) Pour 100 mL of methanol containing 800 mg of dimethylimidazole into the mixed solution of step (1) and stir for 10 min. After standing at room temperature for 12 h, wash the mixture with ethanol by centrifugation several times and dry it in vacuum at 60 °C for 12 h to obtain CNT-Co-MOF.
[0060] (3) CNT-Co-MOF and selenium powder were mixed in a mass ratio of 1:1.8 and kept at 400°C in a nitrogen atmosphere for 2 h to obtain CNT-CoSe2.
[0061] Example 5
[0062] (1) 80 mg of carboxyl carbon nanotubes were ultrasonically dispersed in 60 mL of anhydrous methanol; 10 mg of hexadecyltrimethylammonium bromide was added and stirred for 1 h. Subsequently, 800 mg of cobalt nitrate hexahydrate was dissolved in the above mixed solution;
[0063] (2) Pour 100 mL of methanol containing 1200 mg of dimethylimidazole into the mixed solution of step (1) and stir for 10 min. After standing at room temperature for 24 h, wash the mixture by centrifugation with ethanol several times and dry it in vacuum at 60 °C for 12 h to obtain CNT-Co-MOF.
[0064] (3) CNT-Co-MOF and selenium powder were mixed in a mass ratio of 1:1.9 and kept at 450°C in a nitrogen atmosphere for 2 h to obtain CNT-CoSe2.
Claims
1. Application of a metal compound with adjustable valence as a sulfur catalyst for a lithium-sulfur battery, wherein the preparation of the metal compound with adjustable valence comprises the following steps: Step (1), ultrasonically dispersing carbon nanotubes in anhydrous methanol, adding hexadecyltrimethylammonium bromide and stirring to dissolve, and then adding cobalt nitrate hexahydrate to dissolve to obtain a mixed solution; The carbon nanotubes are functionalized nanotubes containing functional groups; Step (2), pouring methanol containing dimethylimidazole into the mixed solution and stirring, then standing for aging at room temperature, and washing by centrifugation with ethanol to obtain CNT-Co-MOF; the mass ratio of hexadecyltrimethylammonium bromide to carbon nanotubes is 1:5-1:10, the mass ratio of carbon nanotubes to cobalt nitrate hexahydrate is 1:8-1:10, and the mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 1:1-1.5:1; Step (3), after mixing the CNT-Co-MOF and selenium powder, reacting them at 400-600° C. in an inert atmosphere for 2-3 h to obtain CNT-CoSe2; the mass ratio of the CNT-Co-MOF to the selenium powder is 1:1.8-1:
2.
2. The use according to claim 1, characterized in that: The expression of the metal compound with adjustable valence is: CNT-CoSe2; wherein CNT represents carbon nanotubes, and the introduction of CNT makes Co in CoSe2 2+ The content of Co increases 3+ The content of CNT is reduced, thereby regulating the valence state of Co in CoSe2; wherein the CNT is in situ composited with Co-MOF and reacts with selenium powder in an inert atmosphere at a high temperature of 400 to 600 °C to form CNT-CoSe2, and the valence state of Co in CoSe2 is regulated by controlling the type and amount of CNT and the temperature of the reaction with selenium powder.
3. The use according to claim 2, characterized in that: CNT-CoSe2 is mixed with sulfur and used as the positive electrode material of lithium-sulfur battery; alternatively, a sulfur-carbon composite material is used as the positive electrode, CNT-CoSe2 is mixed with PVDF, NMP slurry is added, and coated on a PP diaphragm to obtain a CNT-CoSe2 modified diaphragm, and a lithium sheet is used as the negative electrode to assemble a button battery.
4. The use according to claim 1, characterized in that: The carbon nanotubes are hydroxylated carbon nanotubes or carboxylated carbon nanotubes.
Citation Information
Patent Citations
CoSe2 / NC-CNT / S lithium-sulfur battery positive electrode material and preparation method thereof
CN115692639A